Effects of Q-switched Nd: YAG laser irradiation on the aqueous solution of human albumin and calf-thymus double strand DNA (ctds) - Ali, Nida Hassan (Iraqi Journal of Physics, 2019)
Q-switched lasers widely used in management skin diseases and sometimes its effect may be inadequate or associated with cytotoxicity. The current study aimed to investigate the effect of Q-switched Nd:YAG laser upon cellular elements using in vitro experimental model. Aqueous solutions of human albumin and pure calf thymus double strand deoxyribonucleic acid (ctdsDNA) irradiated with Q-switched Nd:YAG laser at different rates (1, 3 Hz) and time exposure (up to 60 seconds) using 532 nm (400 mJ) and 1064 (1200 mJ) nm wavelength with fixed spot size of 4 mm. The effect of laser irradiation on the albumin solution also studied in the presence of elemental salts of copper, zinc and iron. Q-switched laser irradiation at 532 nm produced albumin molecule damage that potentiated by copper sulfate and variable effect with zinc sulfate. Iron salt stabilized the effect of laser irradiation upon albumin molecule. The effect of laser irradiation at 1064 nm is less than that observed with 532 nm wavelength. ctdsDNA strands are more susceptible to Q-switched Nd:YAG laser radiation when exposed at 532 nm with pulse rate of 3Hz. It concludes that using Q-switched Nd:YAG laser is safe upon the c